Identifikasi Lokasi Rawan Kecelakaan Lalu Lintas (Black Spot) di Kabupaten Purbalingga, Jawa Tengah - SUGIYANTO, Gito; Fadli, Ari (Jurnal Teknik Sipil dan Perencanaan, 2017)
Road safety is a complicated scientific field of transport research due to the random nature of accident occurrence. Traffic accidents impose serious problems to society in terms of medical costs, economic costs (productivity losts), property damage costs, and human costs. Traffic accidents are increasing and still become the main problem of road transport in Indonesia. One effort to improve transportation safety is by determining and handling the black spot locations. The method that used to identify black spot locations is the frequency-crash method. The aim of this research is to identify black spot locations using Upper Control Limit (UCL) method. The study location is in Purbalingga, Central Java, Indonesia. Database of traffic accidents from 1 January 2010 to 31 December 2015 were obtained from Purbalingga Police. Using the equivalent accident number for death victims or fatality is 10, a severe injury is 5, a minor injury is 1, and property damaged only is 1. Seven roads have accident number value greater than the upper control limit value and identified as a black spot location. Black spot location in Purbalingga regency are Jalan Raya Bayeman, Tlahab Lor; Jalan Raya turut Desa Penolih, Jalan Raya turut Desa Bobotsari, Jalan Raya turut Desa Bojongsari, Jalan Raya turut Desa Jetis, Jalan Raya turut Desa Kembangan, and Jalan Raya turut Desa Panican.